Dietary Intakes of Minerals, Essential and Toxic Trace Elements for Adults from Eragrostis tef L.: A Nutritional Assessment - Koubová, Eva; Sumczynski, Daniela; Šenkárová, Lenka; Orsavová, Jana; Fišera, Miroslav (Nutrients, 2018)
This study analysed the contents of thirty-six mineral and trace elements in teff (Eragrostis tef L.) grains. What is more, dietary intakes were calculated. Inductively coupled plasma mass spectrometry (ICP-MS) was used to assess mineral and trace element contents. Consequently, the appropriate Recommended Dietary Allowance (RDA) or adequate intake (AI), and provisional tolerable weekly intake (PTWI) or provisional tolerable monthly intake (PTMI) values for adults were determined according to the Food and Agriculture Organization/World Health Organization (FAO/WHO) and Institute of Medicine (IOM) regulations. Teff is a significant contributor to RDAs and AIs for females in the following order: Mn > Cu > Zn ≥ Mg > Fe ≥ P and Ca. For males, teff contributes in the order, Mn > Cu > Fe > Zn ≥ P ≥ Mg > and Ca. The concentration of arsenic (65.9 µg/kg) in brown teff originating in Bolivia exceeded the average acceptable value set by Reg. No. 1881 of 6-50 µg/kg in cereals consumed in the EU. The PTWIs or PTMIs for Al, Cd, Sn and Hg were all under 7%, which is below the limits of toxic element intake related to the body weight of 65 kg for adult females and 80 kg for males, set by the FAO/WHO. Teff grains can be recommended as a valuable and safe source of minerals and trace elements.
Keywords: Recommended Dietary Allowances; Eragrostis tef; Nutrition Assessment; hodnocení rizik; Female; Edible Grain; jedlá semena; stopové prvky; ženské pohlaví; Eragrostis; výživové doporučené dávky; Trace Elements; nutriční hodnota; Nutritional Status; dietary intakes; lidé; Food Safety; Nutritive Value; Risk Assessment; ICP-MS; hmotnostní spektrometrie; essential trace elements; Minerals; dieta; nutriční stav; minerals; Diet; Male; bezpečnost potravin; Mass Spectrometry; minerály; hodnocení stavu výživy; mužské pohlaví; toxic trace elements; Humans